Opportunities for Carbon Sequestration Benefits from Growing Trees of Medicinal Importance on Farm Lands of Haryana - Gera, Mohit; Chauhan, Suresh (Indian Forester, 2010)
Forestry CDM projects involving afforestation and reforestation offer opportunities for CO2 mitigation by removal of accumulated CO2 in atmosphere and sequester it in vegetation, soil and wood products. Besides being grown for longer periods, tree species of medicinal importance are associated with recurring benefits to the growers, on account of fruits, seeds and other products. The potential of involvement of low income communities in growing these tree species for sustainable economic returns make these plantations a promising activity under CDM framework. The present study on plantation of tree species of medicinal importance such as Amla, Arjun, Bael, Bahera, Harar, Jamun, Neem and Reetha has shown that there is significantly large sequestration potential in the range of 3.05 to 11.01 tons of CO2 per ha per year with corresponding carbon benefits of Rs. 702/- to Rs. 2532/- and Rs. 1404/- to Rs. 5064/- under carbon prices of 5 and 10 per ton of CO2 respectively on annual basis for a project period of 30 years. The study has further shown that the increase in returns due to carbon benefits can motivate the small farmers to opt for plantation of these species on farm bunds. The eligibility requirements of these plantations as required under the definition of Forest’ as accepted by India is also discussed.